Gait in patients with stroke-related hemiparesis and methods of gait assessment - Guzik, Agnieszka; Wolan-Nieroda, Andżelina; Walicka-Cupryś, Katarzyna (European Journal of Clinical and Experimental Medicine, 2016)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Cerebral stroke, a serious complication of cardiovascular system disorders, has become an important medical issue in contemporary societies. Gait disorders in patients after stroke constitute a serious clinical challenge - every year, more than ten thousand patients become seriously disabled as a result of stroke. Locomotor disability is one of stroke’s consequences. Patients with stroke-related hemiparesis often show gait disorders. Hemiparetic gait is characterized with a number of disorders, such as a considerable asymmetry of gait phase time, i.e. step length, or limb load – the healthy leg being overloaded. These disorders result in limiting patients’ everyday activity. Therefore, objective methods of gait analysis are currently being researched. Among gait assessment methods there are clinical, or observation methods – which consist of gait description as related to the normal gait patterns; as well as quantitative, or objective methods – which consist of measuring, description and analysis of chosen parameters of human gait. The aim of the study is to characterise gait in patients with stroke-related hemiparesis, as well as to discuss the methods of its assessment.